PELAKSANAAN KOORDINASI BADAN PELAYANAN TERPADU DAN PENANAMAN MODAL (BPTPM) DENGAN BADAN LINGKUNGAN HIDUP (BLH) TERHADAP PENGURUSAN IZIN GANGGUAN USAHA LAUNDRY (HO) KOTA PEKANBARU - Husaini S.AP; Parjiyana M.Si (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2015)
This study aims to determine the level of objective Implementation Coordination of Badan Pelayana Terpadu and Penanaman Modal (BPTPM) and thenBadan Lingkungan Hidup (BLH) Against Business Interruption Handling Permit Laundry Pekanbaru. Assessment indicators Policies, Plans, Procedures and Work, and Briefing Meeting and Joint Decree. This type of research that is located in the Badan Pelayanan Terpadu and Penanaman Modal (BPTPM) with the Badan Lingkungan Hidup (BLH) Pekanbaru This is a kuantitative, using a method that is used to discover knowledge on the subject of study at a particular moment to reveal empirical facts objective. There are two groups of population samples in this study are servants of Licensing numbered 12 and Employees Division of Environmental Impact Assessment (EIA) amounted to 5 people. Types and techniques of data collection consists of the data perimer, secondary, obesrvasi, interviews, questionnaires and documentation. Based on this analysis technique researchers assess and conclude that the implementation of the Coordination Badan Pelayanan Terpadu andPenanaman Modal (BPTPM) and then Badan Lingkungah Hidup (BLH) Against Business Interruption Handling Permit Pekanbaru City Laundry is in the interval Good Enough. Recommendations to be considered, especially with regard to local laws and regulations regarding the implementation of the permit interruption laundry business in the city of Pekanbaru.